The Effective Use of Information Technology and Interactive Activities to Improve Learner Engagement - Abrar Ullah; Sajid Anwar (MDPI AG, 2020)
Student engagement in the learning process is the key to successful delivery of teaching and learning. Teachers face several challenges to engage learners in different disciplines, including computer science. This research conducts a review of BSc (Computer Science) programmes and introduces interactive activities to enhance learner engagement. The study was conducted using a repeated measure design involving 24 participants. The findings revealed that the use of technology, and collaborative and interactive activities in groups may positively influence learner engagement. The participants' feedback before and after introduction of group tasks and interactive activities showed a significant (p < 0.001) and increasing trend in response to questions-related learner engagement. The participants agreed that their learning experience and engagement enhanced with the use of technology and interactive and collaborative activities.